Beispiel Nr: 02
$ \text{Gegeben:}\\ \text{Kathete} \qquad a \qquad [m] \\ \text{Kathete} \qquad b \qquad [m] \\ \\ \text{Gesucht:} \\\text{Hypotenuse} \qquad c \qquad [m] \\ \\ c =\sqrt{a^{2} + b^{2} }\\ \textbf{Gegeben:} \\ a=6m \qquad b=8m \qquad \\ \\ \textbf{Rechnung:} \\ c =\sqrt{a^{2} + b^{2} } \\ a=6m\\ b=8m\\ c =\sqrt{(6m)^{2} + (8m)^{2} }\\\\c=10m \\ \small \begin{array}{|l|} \hline a=\\ \hline 6 m \\ \hline 60 dm \\ \hline 600 cm \\ \hline 6\cdot 10^{3} mm \\ \hline 6\cdot 10^{6} \mu m \\ \hline 0,006 km \\ \hline \end{array}\\ \small \begin{array}{|l|} \hline b=\\ \hline 8 m \\ \hline 80 dm \\ \hline 800 cm \\ \hline 8\cdot 10^{3} mm \\ \hline 8\cdot 10^{6} \mu m \\ \hline 0,008 km \\ \hline \end{array}\\ \small \begin{array}{|l|} \hline c=\\ \hline 10 m \\ \hline 100 dm \\ \hline 10^{3} cm \\ \hline 10^{4} mm \\ \hline 10^{7} \mu m \\ \hline 0,01 km \\ \hline \end{array}\\$